Syiar Islam di Televisi Lokal: Studi Program Musikalisasi Dakwah Di TVRI Jambi - Nur Isnaini; Muhaimin (Islamic Journalism Department/ Program Studi Jurnalistik Islam, 2022)
This research is motivated by a reality that is concerning and requires attention, namely television shows that contain scenes that are not educational, not entertaining, contain pornographic action and pornography; violence, sadism, mystical and supernatural, unfair and balanced information, not informative, and does not respect the private lives of others. The purpose of this study is to explore how the contents (messages) of the da'wah broadcast program on local television, the impression of the public who witnessed this program and discuss the obstacles and obstacles to the process of producing and broadcasting the Da'wah Musicalization program. The results of this study show that the contents (messages) of Da'wah Musicalization broadcasts are about faith, shari'ah, and morality. The public's impression (image) of the media, sources and messages of the Da'wah Musicalization program is very good and positive. Watching this program can bring changes to the audience's perspectives, attitudes and knowledge of the Islamic religion as well as motivate viewers to improve their behavior in everyday life. So that Musicalization of Da'wah can be an alternative solution and shows worth watching for the community. The inhibiting factors for broadcast production come from human, natural and technical resources. Meanwhile, the obstacle in the field lies in the scheduling of resource persons, which must be different for each broadcast. Furthermore, this method cannot be enjoyed by viewers who are far from the center of Jambi City, such as Kerinci.